Analysis of Customer Loyalty and The Influence of Product Attributes, Promotions and Religious Commitments on The Decision to Choose Saving Products in Sharia Bank Sumut - Muhammad Zuardi; Muslim Marpaung; Irma Suryani Lubis (International ABEC, 2021)
Savings are deposits that can only be withdrawn according to certain agreed conditions, but cannot be withdrawn by cheque, bilyet, demand deposit, and or other equivalent instruments. If the customer wants to take his deposit, he can come directly to the bank with a passbook, withdrawal slip, or through an ATM facility. Deposit customers have more consideration factors than financing customers, who tend to only focus on the amount of financing that must be paid. Financing customers are selected strictly by customers, in contrast to TPF customers who tend to act as selectors of the bank to be selected. This has an impact on bank policies to pay attention to many aspects in increasing the number of customers. Islamic banks as banks that display religious symbols have a target market for Muslim community groups in the process of collecting and distributing funds. Religion is one factor that is highly considered by consumers to decide to become a customer of a sharia bank, there are still many reasons and other factors that can influence consumer considerations to want to become a customer of a sharia bank. One of them comes from the marketing strategy carried out by Islamic banks through the marketing mix strategy.